Institutional Monitoring Of Sticky CEO Compensation - Yang, Daecheon; Mo, Kyoungwon (Journal of Applied Business Research, 2018)
This study examines the monitoring role of institutional investors in both mitigating the degree of downward-sticky CEO compensation and alleviating the undesirable effects of the sticky compensation on shareholder wealth. Particularly, we parallel the literature on “pay for performance” and institutional monitoring role to critically examine the measure of fluctuating pay-for-performance sensitivity, re-characterize the asymmetric compensationperformance link, and then capture managerial rent extraction. We find that sticky CEO compensation is significantly and negatively associated with firm value. Further, we find that institutional ownership decreases the compensation stickiness in underperforming firms and ameliorates its value-deteriorating effect.